Development and verification of a distributed electro-thermal Li-ion cell model - Stocker, Richard; Lophitis, Neophytos; Mumtaz, Asim (My University, 2018)
This paper presents a 1D distributed electro-thermal li-ion cell model. The model is intended to give accurate representation of cell thermal and electrical characteristics in response to current application, highlighting distributions of these parameters across the cell. It is also designed to be compact and fast simulating. A generalized parameterization approach allows the model to be easily adaptable to different cell designs and chemistries. The model achieves this by combining a thermal model based on thermal laws, with an electrical equivalent circuit model, both populated by empirical data accessible through simple individual cell testing. In this paper, the model is explained, and simulation results are correlated against a Nickel Manganese Cobalt (NMC)/graphite cell cycled under constant current and also dynamic conditions without cooling. It was found that the model provides accurate results when compared to a constant current discharge and representative drive test cycle.
Keywords: Battery cell; Lithium-ion; Model; Simulation